PENGHAMBATAN PERTUMBUHAN Aspergillus flavus DAN Fusarium moniliforme OLEH EKSTRAK SALAM (Eugenia polyantha) DAN KUNYIT (Curcuma domestica) - Ira Wulan Dani; Kiki Nurtjahja; Cut Fatimah Zuhra (Saintia Biologi, 2012)
Growth inhibition of Aspergillus flavus and Fusarium moniliforme by leaf extract of salam (Eugenia polyantha) and turmeric (Curcuma domestica) was studied. Kirby-Bauer disc diffusion method was used in this experiment. The plant extracts used were 0, 5, 10, 15, 30, 40, 50, 60 and 70% and dimethyl sulfoxide (DMSO) as a solvent. The result showed that the E. polyantha and C. domestica have a different activity in inhibiting the growth of A. flavus. The leaf extract of turmeric showed lower activity inhibiting A. flavus and F. moniliforme than that of E.polyantha. In 5% E. polyantha inhibits the growth both of the fungus. While C. domestica showed activity inhibiting A. flavus in 5 % and F. moniliforme in 40 %. Keywords: A. flavus, F. moniliforme, extract salam, turmeric